Spatial synchrony of planthopper species with contrasting outbreak behaviour - Grilli, Mariano Pablo (2008)
We studied the synchrony of two sympatric delphacids species with different outbreak behaviours over a range of 250 km in Argentina. 2 The spatial synchrony in the dynamics of D elphacodes kuscheli and T oya propinqua was quantified by collecting individuals of both species simultaneously at three sampling heights: ground, 1.5 m and 6 m above the ground. Synchrony between paired sampling sites separated by increasing distances was estimated using a nonparametric covariance function. 3 A significant difference was found between the spatial synchrony of the species studied. Delphacodes kuscheli individuals collected at 6 m above the ground showed consistent spatial synchrony over long distances with correlation values declining by 40%. Population dynamics showed declining synchrony as site separation increased. Toya propinqua populations did not show this pattern. This species had a lower mean regional synchrony at at 6 m above the ground, but their ground height synchrony was greater than that observed for D. kuscheli. 4 One possible synchronizing mechanism is seasonality and the dispersal strategies of each species. The main host plants of D. kuscheli are winter cereals sown as pasture for cattle grazing and the synchrony of the crop may affect the general pattern of dispersing individuals of this species. The lack of synchrony observed in T. propinqua populations was probably due to the wider host range of this species.